2018
DOI: 10.1111/puar.12904
|View full text |Cite
|
Sign up to set email alerts
|

Providing Public Servants What They Need: Revealing the “Unseen” through Data Visualization

Abstract: Electronic media has enabled new forms of communication with the potential to provide more effective means of conveying evidence to public servants. This article explores what is known about the use of these new capacities in public affairs to visualize the results of research. The authors first explore the value of visual engagement for increasing comprehension. Then, they examine what is known of studies of the effectiveness of visualization and offer basic design principles that underpin effective visualiza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 35 publications
(62 reference statements)
1
17
0
Order By: Relevance
“…Indeed, one study by the United States Department of Education found roughly half of the United States population in 2002 had a difficult time in understanding even basic numerical information (Kirsch et al 2002). Similar findings are also present in recent public management research that assesses how different methods of presentation shape comprehension of government information (Alon-Barkat 2019; Isett and Hicks 2018; Olsen 2017). In general, this nascent line of work reveals that statistical information tends to be more difficult for individuals to recall and ultimately comprehend (Olsen 2017; Porumbescu et al 2017).…”
Section: Hypotheses: Shaping Compliance Intentions Through Comprehensionsupporting
confidence: 80%
“…Indeed, one study by the United States Department of Education found roughly half of the United States population in 2002 had a difficult time in understanding even basic numerical information (Kirsch et al 2002). Similar findings are also present in recent public management research that assesses how different methods of presentation shape comprehension of government information (Alon-Barkat 2019; Isett and Hicks 2018; Olsen 2017). In general, this nascent line of work reveals that statistical information tends to be more difficult for individuals to recall and ultimately comprehend (Olsen 2017; Porumbescu et al 2017).…”
Section: Hypotheses: Shaping Compliance Intentions Through Comprehensionsupporting
confidence: 80%
“…The core graph with the number of contaminations in relation to the number of hospital admissions, and specifically the number of intensive care patients, was and is widely used to check whether hospital systems can cope with the rising number of COVID‐19 patients. This communication fuels the visualization and more specifically the “ graphication ” of politics and policy making (see Isett and Hicks on the impacts of data visualization). The Dutch and Belgian health research agencies announce daily facts and figures on these key parameters.…”
Section: The Staging Of Sciencementioning
confidence: 99%
“…Arguably, government bodies have a 'dubious record on the guardianship of large-scale datasets, the management of contract relationships and large technology-based projects, and capacity to innovate with newer media and technologies in comparison with firms, third sector organisations, and citizens themselves' (Clarke and Margetts, 2014: 409). Hence, they also lag behind in Big Data, although this situation is changing with technological advancements in developing data-driven solutions for policymakers (Isett and Hicks, 2018). In a survey of public managers about the barriers to adopting data analytics, Sims and Sossei (2012) found that the key challenge identified was inadequate budget resources, closely followed by lack of appropriate staff.…”
Section: Organisational Levelmentioning
confidence: 99%